2007
DOI: 10.1016/j.mce.2007.02.008
|View full text |Cite
|
Sign up to set email alerts
|

T3-mediated gene expression is independent of PGC-1α

Abstract: Please cite this article as: Wulf, A., Harneit, A., Weitzel, J.M., T3-mediated gene expression is independent of PGC-1␣, Molecular and Cellular Endocrinology (2007), doi:10.1016/j.mce.2007 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
3
10
1
Order By: Relevance
“…Although recent report indicates that thyroid hormone-mediated gene expression patterns are not completely depending on PGC-1 activation (Wulf et al, 2007), the above data support the idea that a thyroid hormone-mediated activation of PGC-1 might help this coactivator to exert its function in adaptation to endocrine signals. On the other hand, additional factors might contribute to PGC-1 activation in response to other signals, such as low environmental temperature.…”
Section: Discussionsupporting
confidence: 52%
“…Although recent report indicates that thyroid hormone-mediated gene expression patterns are not completely depending on PGC-1 activation (Wulf et al, 2007), the above data support the idea that a thyroid hormone-mediated activation of PGC-1 might help this coactivator to exert its function in adaptation to endocrine signals. On the other hand, additional factors might contribute to PGC-1 activation in response to other signals, such as low environmental temperature.…”
Section: Discussionsupporting
confidence: 52%
“…Since the overall structure of this DBD mutant remains unaffected (Shibusawa et al 2003a), it is likely that a suggested protein-protein interaction domain remains intact. As also suggested for different members of the nuclear receptor family, these proteins are targets of post-translational modifications, which facilitate their function within the transrepression mechanism (Moeller et al 2005, Hiroi et al 2006, Kenessey & Ojamaa 2006, Storey et al 2006, Wulf et al 2007. Further investigations should target these questions with special emphasis on the DBD of TR.…”
Section: Discussionmentioning
confidence: 93%
“…This experiment showed that silencing PGC-1α abolished the ability of T3 to induce PDK4, CPT-1a, PEPCK and C/EBPβ gene expression indicating that PGC-1α is an important coactivator for the T3 induction of these genes in primary hepatocytes. This experiment contrasts with a recent study conducted by Wetizel's group, as they reported that silencing PGC-1α had no effect on the induction of gene expression by T3 in rat pituitary (GC) cells (Wulf et al, 2007). In contrast with our studies, they measured the T3 effect on two other genes, glycerol-3-phosphate dehydrogenase (GPDH) and adenine nucleotide translocater 2 (ANT2).…”
Section: The Role Of the Pgc-1α In The Induction Of The Pdk4 By Thyrocontrasting
confidence: 99%